2021
DOI: 10.1126/science.abb6396
|View full text |Cite
|
Sign up to set email alerts
|

Horizontally transmitted parasitoid killing factor shapes insect defense to parasitoids

Abstract: Interkingdom competition occurs between hymenopteran parasitoids and insect viruses sharing the same insect hosts. It has been assumed that parasitoid larvae die with the death of the infected host or as result of competition for host resources. Here we describe a gene family, parasitoid killing factor (pkf), that encodes proteins toxic to parasitoids of the Microgastrinae group and determines parasitism success. Pkfs are found in several entomopathogenic DNA virus families and in some lepidopteran genomes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Expression of TnAV parasitoid killing factors ORF021 and ORF074 at 6, 12, 24 and 48 h p.i. TnAV-6a1 ORF023 amino acid sequence was found to possess 25.93 % sequence identity to TnAV-2c PKF gene (ORF074) identified in [25], and therefore was included in this figure. The PKF expression patterns are shown for somatic tissues (a) and haemolymph (b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of TnAV parasitoid killing factors ORF021 and ORF074 at 6, 12, 24 and 48 h p.i. TnAV-6a1 ORF023 amino acid sequence was found to possess 25.93 % sequence identity to TnAV-2c PKF gene (ORF074) identified in [25], and therefore was included in this figure. The PKF expression patterns are shown for somatic tissues (a) and haemolymph (b).…”
Section: Resultsmentioning
confidence: 99%
“…SfAV-1a also encodes a PKF gene (ORF032), which is the most highly expressed gene of this ascovirus [10], demonstrating the importance of this protein for eliminating parasitoid larvae that would compete with the virus for host resources. In an interesting 1985 study [40], strong evidence was provided that SfAV was capable of killing larvae of the parasitoid, Cotesia marginiventris , when both occurred together in larvae of S. frugiperda [25], showed that related killing factors were encoded in the genomes of several Spodoptera species, suggesting that these PKFs were acquired by horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNAi is a non-invasive way of delivering dsRNA into insects to knockdown specific gene expression 54 57 . We have shown that injecting RNAi is feasible and can suppress the transcription level of target genes in FAW larvae.…”
Section: Discussionmentioning
confidence: 99%